The Expertise Skills of a Forensic Accountant - Wahyuni-TD, I., S,; bin Zainuddin, Yuserrie; Haron, Hasnah (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
The forensic accountant has roles, knowledge and skills. The purpose of skills by forensic accountants is to investigate financial irregularities, uncover fraud, and provide expert analysis and testimony in legal proceedings. This paper aims to review necessary skills possessed by forensic accountants. There are top five essential traits and characteristics ranked the forensic accountants in the public sector which need to possess; analytical, ethical, detail oriented, onfident and evaluative. All these findings are consistent with another study conducted by AICPA, USA which stated that forensic accountant in the private sector should be analytical, detail-oriented and ethical. In fact, as businesses and financial transactions become increasingly complex, the risk of fraud and financial misconduct also increases. A high demand of accounting profession skills globally to examine progressively the existence of frauds.